HEPATO PROTECTIVE EFFECT OF AQUEOUS EXTRACT OF PIPER LONGUM AND PIPERINE WHEN ADMINISTERED WITH ANTITUBERCULAR DRUGS - PREMA GURUMURTHY,; S. VIJAYALATHA,; A. SUMATHY,; M. ASOKAN,; M. NASEEMA, (The Bioscan, 2012)
The objective of the study was to assess the hepatoprotective effect of aqueous extract of Piper longum and piperine when administered with normal dosage of antitubercular drugs. The parameters assessed were lipid peroxidation and levels of reduced glutathione in liver homogenate. Histopathological studies of liver was also carried out. Reduced glutathione levels were significantly decreased (p<0.001) and lipid peroxidative products levels were significantly increased (p<0.001) in the group treated with antitubercular drugs compared to controls. Administration of aqueous extract of Piper longum or piperine with antitubercular drugs significantly increased the reduced glutathione levels (p<0.001) and decreased lipid peroxidation (p<0.001). Histopathological studies indicate no significant change between the control and the group administered with antitubercular drugs. Even in studies carried out with Piper longum extract in infected animals, administration of antitubercular drugs significantly increased lipid peroxidation (p<0.001) and decreased reduced glutathione levels (p<0.05). Administration of aqueous extract of Piper longum with antitubercular drugs significantly increased the reduced glutathione levels (p<0.001) and decreased lipid peroxidation (p<0.001). The results indicate that administration of anti TB drugs in normal doses for a period of 45 days does not cause significant histopathological changes in liver but decreases the reduced glutathione levels and increases lipid peroxidation. This change in antioxidant status is prevented on administration of Piper longum aqueous extract and piperine with antitubercular drugs, thus proving their hepatoprotective effect.